Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1203/00006450-199904010-00016
|View full text |Cite
|
Sign up to set email alerts
|

Central Motor Reorganization in Cerebral Palsy Patients with Bilateral Cerebral Lesions

Abstract: Transcranial magnetic stimulation (TMS) has been used to describe cortical plasticity after unilateral cerebral lesions. The objective of this study was to find out whether cortical plasticity occurs after bilateral cerebral lesions. We investigated central motor reorganization for the arm and leg muscles in cerebral palsy (CP) patients with bilateral cerebral lesions using TMS. Seventeen patients (12 with spastic diplegia, 1 with spastic hemiplegia, and 4 with athetoid CP) and 10 normal subjects, were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 44 publications
5
45
0
1
Order By: Relevance
“…By stimulating at a number of different scalp positions (using a stimulus intensity close to MEP threshold) and measuring the amplitude of the MEP at each site, it is possible to assess the location of the optimal position for stimulation and the center-of-gravity, which defines the mean position of the map (Abbruzzese and Trompetto, 2002;Chen, 2000). Only one study has examined cortical maps in a small group of typically developing children, 6 to 14 years of age, as a comparison for children with cerebral palsy (Maegaki et al, 1999). Cortical representation sites for the tibialis anterior, biceps brachialis, and abductor pollicis brevis muscle were identified between 1 to 4 cm, 4 to 6 cm, and 5 to 8 cm lateral to the cranial vertex, respectively; the authors did not report the optimal stimulation site or the center of gravity.…”
Section: Cortical Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…By stimulating at a number of different scalp positions (using a stimulus intensity close to MEP threshold) and measuring the amplitude of the MEP at each site, it is possible to assess the location of the optimal position for stimulation and the center-of-gravity, which defines the mean position of the map (Abbruzzese and Trompetto, 2002;Chen, 2000). Only one study has examined cortical maps in a small group of typically developing children, 6 to 14 years of age, as a comparison for children with cerebral palsy (Maegaki et al, 1999). Cortical representation sites for the tibialis anterior, biceps brachialis, and abductor pollicis brevis muscle were identified between 1 to 4 cm, 4 to 6 cm, and 5 to 8 cm lateral to the cranial vertex, respectively; the authors did not report the optimal stimulation site or the center of gravity.…”
Section: Cortical Mapsmentioning
confidence: 99%
“…Cortical maps of the lower extremity muscles are laterally displaced in children born prematurely who have PVL and spastic diplegia. In contrast, maps of lower extremity muscles are normally placed in individuals born at term who have spastic diplegia and in those with a bilateral dyskinetic form cerebral palsy, neither of which are associated with abnormalities resulting from ischemia of central white matter (Maegaki et al, 1999).…”
Section: Cerebral Palsymentioning
confidence: 99%
“…Furthermore, TMS studies have reported changes in motor pathways at the subcortical level, and a number of these studies focused on the ipsilateral motor pathway from the unaffected motor cortex to affected extremities, through the transcallosal pathway, the anterior CST, and pathways synapsed in the brainstem, such as the reticular formation [1,2,3,4,5,6,21,22,23,24]. However, the TMS is limited by an inability to visualize neural tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted on neural pathway changes at the subcortical level following brain injury [1,2,3,4,5,6,7,21,22,23,24]. Furthermore, TMS studies have reported changes in motor pathways at the subcortical level, and a number of these studies focused on the ipsilateral motor pathway from the unaffected motor cortex to affected extremities, through the transcallosal pathway, the anterior CST, and pathways synapsed in the brainstem, such as the reticular formation [1,2,3,4,5,6,21,22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…7 Nevertheless, there are case reports on the use of fMRI alone or in combination with transcranial magnetic stimulation, which investigated different aspects of cortical reorganization in children with CP. [8][9][10][11][12][13][14] Although CP is thought to originate mostly from subcortical lesions and less often from cortical ones, 8 there is evidence that associated plasticity changes occur in the motor cortex. [9][10][11][12][13][14] Certain differences in cortical activation patterns have emerged from these studies between healthy and children with CP.…”
Section: Introductionmentioning
confidence: 99%